SMOC Binds to Pro-EGF, but Does Not Induce Erk Phosphorylation via the EGFR. - J Terrig Thomas; Lina Chhuy-Hy; Kristin R Andrykovich; Malcolm Moos (PLoS ONE, 2016)
In an attempt to identify the cell-associated protein(s) through which SMOC (Secreted Modular Calcium binding protein) induces mitogen-activated protein kinase (MAPK) signaling, the epidermal growth factor receptor (EGFR) became a candidate. However, although in 32D/EGFR cells, the EGFR was phosphorylated in the presence of a commercially available human SMOC-1 (hSMOC-1), only minimal phosphorylation was observed in the presence of Xenopus SMOC-1 (XSMOC-1) or human SMOC-2. Analysis of the commercial hSMOC-1 product demonstrated the presence of pro-EGF as an impurity. When the pro-EGF was removed, only minimal EGFR activation was observed, indicating that SMOC does not signal primarily through EGFR and its receptor remains unidentified. Investigation of SMOC/pro-EGF binding affinity revealed a strong interaction that does not require the C-terminal extracellular calcium-binding (EC) domain of SMOC or the EGF domain of pro-EGF. SMOC does not appear to potentiate or inhibit MAPK signaling in response to pro-EGF, but the interaction could provide a mechanism for retaining soluble pro-EGF at the cell surface.